Nitric Oxide Bioavailability and Insulin Resistance: An Overview - Kobayashi, Jun (Challenges and Advances in Pharmaceutical Research Vol. 8, 2022)
The aim of this review are to discusses the mechanisms by which insulin resistance develops in the presence of increased adiposity, to summarize the causative relationship between impaired NO bioavailability and insulin resistance, and also to show the implications of life-style changes to prevent insulin resistance. Obesity with increased visceral adiposity is an inflammatory condition that leads to insulin resistance. Because the insulin signalling pathway is linked to endothelial nitric oxide synthase (eNOS) activation, insulin resistance is always associated with decreased nitric oxide (NO) bioavailability. Recently, accumulating evidence has suggested that physical exercise and dietary nitrate/nitrite diets rich in vegetables improve insulin resistance by enhancing NO bioavailability, and thus provide potential preventive and therapeutic options for these patients with insulin resistance.